Pemberdayaan UMKM melalui Program Distribusi Takjil di Kota Lhokseumawe Aceh - Fikri, Ahmad; Muarif, Agam; Razi, Ar (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
Muslims always giving infaq in the month of Ramadan. Infaq is one of the Islamic economic sectors that plays a role in the social sector. The management of infak must be effective to maintain the trust of Muslims who provide funds. One of the problems of infak management is distribution among all circles of society. Currently, the community can distribute infaq through community institutions. The funds collected are then distributed in the form of takjil through volunteers throughout Indonesia, especially in mosques around the city of Lhokseumawe, Aceh Province. The method of service method used is in the form of community participation starting from collecting funds from the community, making takjil through UMKM Pasar Cunda Lhokseumawe City, distribution of takjil by team of community service Malikussaleh University and acceptance of takjil by four mosques around the city of Lhokseumawe. The purpose of this activity is to raise funds from the community, empower local UMKM and share fellow Muslims in Lhokseumawe City.